2009
DOI: 10.1002/tcr.20171
|View full text |Cite
|
Sign up to set email alerts
|

Flexible host frameworks with diverse cavities in inclusion crystals of bile acids and their derivatives

Abstract: We have systematically investigated structures and properties of inclusion crystals of bile acids and their derivatives. These steroidal compounds form diverse host frameworks having zero-, one- and two-dimensional cavities, causing various inclusion behaviors towards many organic compounds. The diverse host frameworks exhibit the following guest-dependent flexibility. First, the frameworks mainly depend on the included guests in size and shape. The size-dependence is quantitatively estimated by the parameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It was observed that the steroidal ring systems, being rigid, have very similar conformations in all structures, whereas the conformations of the side chains were different. The conformation of the bile acid side chain can be described based on the combination of the dihedral angles C13–C17–C20–C22, C17–C20–C22–C23, C20–C22–C23–C24, and C22–C23–C24–N (Table , for assignments of the steroidal directions see Nakano et al and Miyata et al). When compared with other crystal structures, the side chain conformation of LC‐ L A‐OH ( 9 ) showed a nearly orthogonal turn (87° between the planes through C10–C13–C20 and C23–C24–C25) on the lipophilic back‐side of the steroidal skeleton (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the steroidal ring systems, being rigid, have very similar conformations in all structures, whereas the conformations of the side chains were different. The conformation of the bile acid side chain can be described based on the combination of the dihedral angles C13–C17–C20–C22, C17–C20–C22–C23, C20–C22–C23–C24, and C22–C23–C24–N (Table , for assignments of the steroidal directions see Nakano et al and Miyata et al). When compared with other crystal structures, the side chain conformation of LC‐ L A‐OH ( 9 ) showed a nearly orthogonal turn (87° between the planes through C10–C13–C20 and C23–C24–C25) on the lipophilic back‐side of the steroidal skeleton (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…[47][48][49] Another appealing solid-state property, which leads to remarkable lattice stabilization patterns, is their side chain modification. Modifications of side chains in bile acids have been extensively reviewed [50][51][52][53][54] and unarguably the conformations adopted by side-chains has represented wide range of applications in the field of crystal engineering, co-crystals, improved biological activity, and pharmaceutical applications. In the current study, inspired by the gelation properties, single crystals of N-ethylamide derivatives of lithocholic acid (1), deoxycholic acid (2) and cholic acid (3) were grown from acetonitrile by solvent evaporation to study the effect of inclusion of amide functionality to the hydrogen bonded bilayers.…”
Section: Microscopymentioning
confidence: 99%
“…Cholic acid is a very effective inclusion host and also yields more than one crystal form. 25,26 This report explores the crystallisation behaviour of the simple tetraester 3 that also has a dish-shaped topology.…”
Section: Introductionmentioning
confidence: 99%